2012
DOI: 10.1103/physrevb.85.064101
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the elastic response of binary early transition metal nitrides

Abstract: Motivated by an increasing demand for coherent data that can be used for selecting materials with properties tailored for specific application requirements, we studied elastic response of nine binary early transition metal nitrides (ScN, TiN, VN, YN, ZrN, NbN, LaN, HfN, and TaN) and AlN. In particular, single crystal elastic constants, Young's modulus in different crystallographic directions, polycrystalline values of shear and Young's moduli, and the elastic anisotropy factor were calculated. Additionally, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
83
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 64 publications
20
83
3
1
Order By: Relevance
“…[45] is significantly higher than the experimentally found in-plane (Fig. 5) and out-of-plane moduli ( Table 1, region A).…”
Section: Discussion On the Complexity Of The Cross-sectional Relationcontrasting
confidence: 60%
“…[45] is significantly higher than the experimentally found in-plane (Fig. 5) and out-of-plane moduli ( Table 1, region A).…”
Section: Discussion On the Complexity Of The Cross-sectional Relationcontrasting
confidence: 60%
“…12 Recently, alloys of VN with cubic MoN or WN were predicted to provide higher hardness and ductility (i.e., higher toughness) than VN; 14,15 a result which has been confirmed experimentally for VMoN alloys by Kindlund et al 16 Despite extensive engineering applications, studies of the VN elastic constants are scarce, with reported experimental elastic constants, obtained using acoustic microscopy, 17,18 and theoretical results based on density functional theory, 19,20 differing by up to $150 GPa ($30%). Here, we determine VN elastic constants using subpicosecond ultrasonic optical pump/probe measurements, carried out on single-crystal stoichiometric VN(001), VN(011), and VN(111) thin films.…”
Section: Introductionmentioning
confidence: 94%
“…This development shows the trend that functional materials demand more and more interface research, because possibilities for applications increase. Representative examples of present research on inorganic interfaces are thermal-barrier coatings (TBC) [27][28][29][30], hard TiN-coating [31][32][33][34][35], superconductors [36], and as functional components in microelectronics [37][38][39][40][41][42], transparent conducting oxides (TCO) [43][44][45][46], photovoltaic materials [47], thermo-electrics [48][49][50][51][52], ferroelectrics [53], magnetic materials or spintronics [54,55].…”
Section: Introductionmentioning
confidence: 99%